Effect of comonomer sizes on the strain-induced crystal nucleation of random copolymers. (August 2016) - Nie, Yijing; Gao, Huanhuan; Wu, Yixian; Hu, Wenbing
Graphical abstract: Highlights: Modeling of sequence defects in strain-induced crystal nucleation of copolymer. Comonomer sizes are reflected by the sliding mobility in the crystalline region. Large comonomers hinder intermolecular crystal nucleation induced by strain. Abstract: We performed dynamic Monte Carlo simulations of random copolymers containing variable sliding mobility of non-crystallizable comonomer sequences (reflecting their relative sizes) in the crystalline monomer regions. Upon raising strains, we observed that the comononer sliding mobility does not affect the strain evolution curves of crystallinity. However, in the middle temperature region, the low mobility causes a delay of switching from the intra-molecular to the inter-molecular modes of crystal nucleation in the copolymers holding low fractions of comonomers. We attributed the effect to the difficulty of comonomers to be excluded from the nucleating domains that are limited by sequence segregation in the oriented amorphous segments. The implication of this effect to the efficiency of crystal nucleation upon cyclic loading has been discussed.